Karen's newspaper - Martin, Ann M.; Tang, Susan; Scholastic Inc.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1993)
Karen and her friends start their own neighborhood newspaper, but they learn about ethics in journalism after printing secrets about their neighbors and upsetting everyone.
"A Little Apple paperback."
Source: Copyright deposit, Jan. 14, 1994.